The cultural logic of politics in mainland China and Taiwan - Shi, Tianjian (New York, NY : Cambridge University Press, 2015)
"This title uses surveys, statistics, and case studies to explain why and how cultural norms affect political attitudes and behavior"--
Introduction -- Part I. Theory of Popular Culture: 1. Political culture theory and regime stability; 2. Cultural norms in the East and West; 3. Measuring cultural norms in mainland China and Taiwan; 4. The relationship among culture, structure, and institutions -- Part II. Culture's Impact on Political Attitudes and Behaviors: 5. Culture's impact on political trust; 6. Cultural impacts on political participation; 7. The impace of culture on understandings of democracy -- Conclusion and theoretical reflection.
Includes bibliographical references (pages 261-282) and index.
Print version resource.
eBooks on EBSCOhost
Keywords: Politics and culture -- China; Politics and culture -- Taiwan; Political culture -- China; Political culture -- Taiwan; Political sociology; Politique et culture -- Chine; Politique et culture -- Taiwan; Sociologie politique; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; Political culture; Political sociology; Politics and culture; China; Taiwan